PARADIPLOMACY AND THE FUTURE OF SMART CITY: THE CASE OF SISTER CITY COOPERATION BETWEEN MAGELANG CITY-TULA CITY - Noormansyah, Reza; Akhni, Ghaziah Nurika; Widyantoro, Sigid; Saputra, Hendra Lana (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2024)
This research analyzes the sister city cooperation between Magelang City-Tula City using three layers of paradiplomacy. The layers determine the focus of cooperation and its potential for future smart city implementation in Magelang City. Paradiplomacy has become a promising instrument in the context of sister-city cooperation proposed by regional governments, mostly in forging relations with global cities. Although paradiplomacy is considered the practice of ‘high politics’, various sectors can be operated within the activity, including trades, education, culture, tourism, and technology. As qualitative research, the data was gathered through field and literature studies. Findings highlight that the cooperation has not been further performed by related regional offices beyond the agreement stage (Letter of Intent). Therefore, little can be measured about the impacts it has brought to Magelang City's development, particularly in the pursuit of smart city adoption. Regardless, improvement and programs related to the second layer of paradiplomacy through sister-city cooperation might benefit the Magelang City government in smart city implementation.